District Consolidation and Rural School Closure: E Pluribus Unum? - David Post; Amy Stambach (Journal of Research in Rural Education, 1999)
We analyze the debate over the closure ofa rural Pennsylvania high school and the subsequent consolidation ofits students in a much larger, unified school within the state's largest geographic school district. Our investigation is based on historical research in Clinton County; on interviews with parents, alumnae, administrators, and board members of Keystone Central School District; and on the results ofsurvey we mailed to 550 parents. Our case study highlights a deeper and enduring social tension that is reflected in the conflict: the strain between the centralizing movements of governing bodies and the decentralizing interests of local communities which seek to retain and to define their own identity.